2013
DOI: 10.1136/bmjqs-2012-001778
|View full text |Cite
|
Sign up to set email alerts
|

Surgical technology and operating-room safety failures: a systematic review of quantitative studies

Abstract: Equipment-related failures form a substantial proportion of all error occurring in the OR. Those procedures that rely more heavily on technology may bear a higher proportion of equipment-related error. There is clear benefit in the use of preoperative checklist-based systems. We propose the adoption of an equipment check, which may be incorporated into the current WHO checklist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 40 publications
1
55
0
3
Order By: Relevance
“…Since laparoscopic cholecystectomy is usually performed in approximately an hour and in general is being considered as one of the lesser advanced procedures in surgery, this rate seems also comparable to the 6.3-8.5 equipment-related disturbances we found. Nevertheless, although it is known that laparoscopic surgery is prone to instrumentrelated disturbances [9], this number leaves substantial room for improvement, and apparently this needs to be realized by other solutions than performing minimal invasive surgery in an integrated OR instead of a conventional OR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since laparoscopic cholecystectomy is usually performed in approximately an hour and in general is being considered as one of the lesser advanced procedures in surgery, this rate seems also comparable to the 6.3-8.5 equipment-related disturbances we found. Nevertheless, although it is known that laparoscopic surgery is prone to instrumentrelated disturbances [9], this number leaves substantial room for improvement, and apparently this needs to be realized by other solutions than performing minimal invasive surgery in an integrated OR instead of a conventional OR.…”
Section: Discussionmentioning
confidence: 99%
“…This resembles 23.5 % of the errors in the OR [9]. Additionally, they found that procedures that are more dependent on technology and/or equipment tended to show approximately three times higher equipment-related error rates [9]. Furthermore, during laparoscopic surgery, 47 % of the communication is equipment related, compared with 39 % during open surgery [10].…”
mentioning
confidence: 94%
“…A previous study has shown that there is a large amount of hazards throughout the entire delivery process of surgical instruments 15. The unavailability of surgical instruments represented around 40% of equipment-related incidents in the OR 16 17. Each incident induces an average of 12 min of extra work for the OR team and 5 min of delay,16 and moreover, it increases the potential for errors in the OR 18 19.…”
Section: Introductionmentioning
confidence: 99%
“…An English study admitted that 16% of patients hospitalized are victims of some kind of medical error and that half of these errors are attributed either to mistakes regarding procedures that precede the surgery or to technological and equipment failures 7 . In France, medical errors are seen and studied rigorously and the legal system has already identified the most common errors considering their typology.…”
Section: Nuances and Challenges Of Medical Malpractice Inmentioning
confidence: 99%
“…The evolution of medical sciences has made available a major technological framework to benefit humans 1,[2][3][4][5][6][7] . Brazil currently sees an abrupt increase in the search for clinical interventions, whose justifications range from those which are truly needed to others targeting aesthetical improvements 8 .…”
Section: Nuances and Challenges Of Medical Malpractice In Brazil: Vicmentioning
confidence: 99%